Mapping the complex systems that connects the urban environment to cognitive decline in adults aged 50 years and older: a group model building study. (November 2022) - Avila-Palencia, Ione; Garcia, Leandro; Cleland, Claire; McGuinness, Bernadette; Meehan, Conor; Hunter, Ruth F; ,
Abstract: Background: A supportive urban environment can prevent or delay the progress of cognitive decline. There is evidence for the existence of mechanistic pathways between the urban environment and cognitive decline, but the interrelations between these pathways are unclear. In this study, we aimed to map the mechanistic pathways by which urban environment factors affect cognitive decline in adults older than 50 years. Methods: This group model building study was part of the Supportive environments for Physical and social Activity, healthy ageing, and CognitivE health (SPACE) project. We held a 2-day workshop with theSPACE investigators based on the Group Model Building (GMB) methodology. The workshop aimed to create a causal-loop diagram (CLD) that identifies established and potential urban environment, lifestyle, health, and physiological determinants of cognitive decline in adults older than 50 years, and the dynamic interrelations between these factors. A facilitation team guided the activities (IA-P, LG, CM, and RFH). The workshop was held online following appropriately adapted scripts. After the workshop, the modelling team reviewed the CLD to ensure that main potential causal pathways and mechanisms were captured. Findings: The workshop ran from Dec 6–7, 2021, and 12 experts from ten different disciplines identified 83 factors and 221 connections between them. After review, the CLD presented 45 factors and 110 connections. All factors were classified in ten main domains: urban design (eg, walkability), social environment (eg, social relationships), travel behaviours (eg, active travel), by-products (eg, air pollution), lifestyle (eg, recreational physical activity), mental health (eg, stress), disease or physiology (eg, molecular risk), exogenous factors (eg, industrial pollution sources), and cognitive decline outcomes (eg, dementia). The main output was a CLD of the complex system of how the urban environment can influence cognitive decline in older adults, created by, and agreed with, the SPACE investigators. Interpretation: Our findings suggested that GMB can engage experts and help them view problems, such as the determinants of cognitive decline in adults, through the lens of complex systems. Funding: UK Research and Innovation.